Smart i-Bot / Emily Christ Berd, Nur Amerah Azeerah Mohd Zaidon … [et al.] - BERD, EMILY CHRIST; MOHD ZAIDON, NUR AMERAH AZEERAH; MAHYUDIN, NUR AISHAH; MOHD AZAHAR, PUTRI NATASHA AQILAH; MOHD SHAUFI, SITI NADHIRAH (2018)
This Smart i-Bot use to purify the air in home giving cleaner air assist by beeper and makes home more secure. Beeper is static air quality detector functioning in detect the presence of air pollutants in the air. If the percentage air quality is low, beeper will transmit signals to Smart i-Bot to purify the air. This will maintain the air quality efficiently. The filter pad made up with active carbon from coconut shell which effective in trap fine particles of chemicals, dust and allergen in the air. Smart i-Bot can link with mobile phone by install the apps making easier for users monitor status of air quality of the house. This air purifier moves around the home space to purify and maintaining the air quality assist by beeper and sum up the report of air quality status and send to mobile phone through Wi-Fi connection. As indirectly user also can access the security camera of Smart i-Bot from anywhere on mobile phone apps. This method sends the data over a local network so that you can view from anywhere on network in real time. This project makes the air purifier notify the user about latest update about air quality status in their home and improve your home security.